Relationship Between Egg Weight and Hatch Weight in Pigeons (Columba livia) - Ibrahim, T.; Sani, Y. (International Journal of Poultry Science, 2010)
This study was undertaken to assess the relationship between egg weight and hatch weight in pigeons and also derive prediction equation based on the relationship. It was conduced in nine randomly selected households in Misau town of Bauchi State, Nigeria, between April and November 2009. The mean egg weight and squab hatch weight were 14.46±0.11 g and 12.55±0.08 g, respectively. No significant differences were detected in egg weight and squab hatch weight when compared on the basis of order of lay. The two traits were strongly correlated (r = 0.932). The study has shown that body weight of squabs at hatching is to a large extent determined by the weight of the egg (R2 = 86.9%) and can be predicted using the latter with a high degree of precision.